World Rabies Day 2022 in Machakos, Kenya - International Livestock Research Institute (International Livestock Research Institute, 2022)
The ILRI led One Health Centre in Africa (OHRECA) celebrated World Rabies Day on September 28 2022, by organizing a dog vaccination exercise in Machakos county, Kenya. World Rabies Day aims to raise awareness and advocate for rabies elimination globally. This year’s theme is One Health, Zero Deaths.